Substance use disorders and medical comorbidities among high-need, high-risk patients with diabetes. (1st May 2018) - Wu, Li-Tzy; Ghitza, Udi E.; Zhu, He; Spratt, Susan; Swartz, Marvin; Mannelli, Paolo
Highlights: Adults with multi-comorbidities are super utilizers of healthcare resources. Substance use disorders (SUDs) are understudied in high-risk, high-need populations. Many (48%) high-risk diabetes adults had SUD recorded in their medical records. Other mental health disorders (75%) also were common in high-risk diabetes adults. The results stress a need to optimize high-risk behavioral health care management. Abstract: Background: The majority of the U.S. healthcare resources are utilized by a small population characterized as high-risk, high-need persons with complex care needs (e.g., adults with multiple chronic conditions). Substance use disorders (SUDs) and mental health disorders (MHDs) are a driver of poor health and additional healthcare costs, but they are understudied among high-need patients. Objective: We examine the prevalence and correlates of SUDs and MHDs among adults with high-risk diabetes, who are patients at the top 10% risk score for developing poor outcomes (hospital admission or death). Methods: A risk algorithm developed from Duke University Health System electronic health records (EHRs) data was used to identify patients with high-risk diabetes for targeting home-based primary care. The EHR data of the 263 patients with high-risk diabetes were analyzed to understand patterns of SUDs and MHDs to inform care-coordinating efforts. Results: Both SUDs (any SUD 48.3%, alcohol 12.5%, tobacco 38.8%, drug 23.2%) and MHDs (any MHD 74.9%, mood 53.2%, sleep 37.3%, anxiety 32.7%, schizophrenia/psychotics/delusional 14.8%, dementia/delirium/amnestic/cognitive 14.4%, adjustment 9.1%) were prevalent. Overall, 81.7% of the sample had SUD or MHD. Elevated odds of SUD were noted among men (tobacco, alcohol) and those who were never-married (alcohol, cannabis). African-American race (vs. other race/ethnicity) was associated with lower odds of anxiety disorders. Conclusion: While data are limited to one large academic health system, they provide clinical evidence revealing that 82% of patients with high-risk diabetes had SUD and/or MHD recorded in their EHRs, highlighting a need for developing service models to optimize high-risk care.